TEKNIK PENGEMBANGAN KEPEMIMPINAN BERBASIS INTERVENSI DAN KELOMPOK - Rambe, Mahadi Kesuma; Rudianto, Rudianto; Gunawan, Gunawan; Harahap, Amin (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2025)
ABSTRACT The main focus lies on the effectiveness of individual approaches such as coaching, mentoring, and self-leadership training, as well as group approaches through team training, reflective discussions, and collaborative learning. Individual interventions help shape the personal dimensions of leadership, including self-awareness, value orientation, and reflective decision-making, while also strengthening character and internal motivation. Meanwhile, group interventions enhance the social aspects of leadership, such as communication, teamwork, and conflict resolution, consistently improving collective skills and interpersonal sensitivity. This study is a literature review aimed at analyzing leadership development techniques based on individual and group interventions using Indonesian journal and scholarly article sources. The method employed is a library study with a descriptive-qualitative approach. The stages include topic selection, identification and collection of literature from accredited sources, and thematic content analysis to categorize types of interventions and their impacts on leadership development. A total of 20 sources were examined in this study. The results indicate that a combination of individual and group interventions has the potential to develop leaders who are adaptive, reflective, and responsive to workplace dynamics. An integrated approach is recommended as a practical and sustainable leadership development strategy across sectors. These findings provide both theoretical and practical foundations for institutions in designing context-based and evidence-based leadership programs. The study also opens opportunities for further empirical research to evaluate the effectiveness of intervention models in real-world settings. ABSTRAK Fokus utama terletak pada efektivitas pendekatan individual seperti coaching, mentoring, dan pelatihan self-leadership, serta pendekatan kelompok melalui pelatihan tim, diskusi reflektif, dan pembelajaran kolaboratif. Intervensi individual membentuk aspek personal pemimpin, seperti kesadaran diri, orientasi nilai, dan pengambilan keputusan reflektif, serta memperkuat karakter dan motivasi internal. Sementara itu, intervensi kelompok mengembangkan aspek sosial kepemimpinan, termasuk komunikasi, kerja sama tim, dan resolusi konflik, dengan hasil yang konsisten dalam meningkatkan kemampuan kolektif dan sensitivitas interpersonal. Penelitian ini merupakan kajian literatur yang bertujuan untuk menganalisis teknik pengembangan kepemimpinan berbasis intervensi individual dan kelompok dengan menggunakan sumber-sumber jurnal dan artikel ilmiah Indonesia. Metode yang digunakan adalah studi pustaka dengan pendekatan deskriptif-kualitatif. Tahapannya meliputi penentuan topik, identifikasi dan pengumpulan literatur dari sumber terakreditasi, serta analisis isi tematik untuk mengelompokkan jenis intervensi dan dampaknya terhadap pengembangan kepemimpinan. Sebanyak 20 sumber digunakan dalam kajian ini. Hasil studi literatur menunjukkan bahwa kombinasi intervensi individual dan kelompok berpotensi membentuk pemimpin yang adaptif, reflektif, dan responsif terhadap dinamika kerja. Pendekatan terpadu direkomendasikan sebagai strategi pengembangan kepemimpinan yang aplikatif dan berkelanjutan di berbagai sektor. Temuan ini memberikan dasar teoretis dan praktis bagi institusi dalam merancang program kepemimpinan berbasis konteks dan bukti. Kajian ini juga mendorong penelitian lanjutan yang bersifat empiris untuk menguji efektivitas model intervensi di lapangan.